The profile of patients with venous leg ulcers: A systematic review and global perspective. Issue 1 (February 2021) - Gethin, G.; Vellinga, A.; Tawfick, W.; O'Loughlin, A.; McIntosh, C.; Mac Gilchrist, C.; Murphy, L.; Ejiugwo, M.; O'Regan, M.; Cameron, A.; Ivory, J.D.
Abstract: Background: A holistic profile that includes demographic, medical history and wound characteristics of individuals with venous leg ulceration is lacking. Lack of such a profile negatively impacts the ability to develop interventions to improve patient outcomes. Objectives: To describe the profile of the patient population with venous leg ulceration from published observational (non-interventional) studies and to identify gaps in the knowledge base for future research in this area. Methods: A systematic review of observational studies that included more than 50 patients, from any world region, of any age and in any care setting. Results: twenty studies, involving 3395 patients, from all world regions met our criteria. Demographic characteristics were well reported and showed a female to male ratio of 1.2:1, average age of 47–65 years, high levels of co-morbidities including hypertension (53–71%) and diabetes (16–20%), and only one study reporting ethnicity. When reported, approximately 4–30% had high levels of depression. The average wound size was 18.6–43.39 cm 2 ; mean wound duration was 13.8–65.5 months, mean number of recurrences was four. No study reported on demographic factors plus medical history plus wound characteristics together. Conclusion: a comprehensive, holistic profile of the population with VLU is lacking. There is a critical need for more comprehensive profiling to enable the development of targeted interventions to improve outcomes. Highlights: Venous leg ulcer patient profiles from five global regions vary in comprehensiveness. Overall, a comprehensive characterisation of this population has not been documented. Profile: female, >65, obese, multiple comorbidities, risk of cardiovascular events.